BUSINESS DEVELOPMENT STRATEGY AT PT.HALALFROZ INDONESIA - Desri Septiyani, Filza; Akhmad Mahbubi; Rahmi Purnomowati; Dewi Rohma Wati (International Journal of Business and Quality Research, 2025)
This study aims to identify and analyze internal and external factors that influence the business development of PT. Halalfroz Indonesia; analyze the company's position that influences the business development of PT. Halalfroz Indonesia; formulate appropriate business development strategy alternatives for PT. Halalfroz Indonesia; determine business development strategy priorities for PT. Halalfroz Indonesia. The types of data used in this study are qualitative and quantitative data from primary and secondary sources. The analysis methods used are the IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSP matrix. The results of the study show that there are 18 key internal factors and 16 key external factors. Based on the weighting and ranking results, the IFE matrix score is 3.009, and the EFE matrix score is 2.897. Based on the IE matrix, PT. Halalfroz Indonesia is positioned in quadrant IV, which is growing and being built with an intensive and integrative strategy. Based on the results of the strategy priority analysis using the QSP matrix, it shows that PT. Halalfroz Indonesia's main priority strategy is to form a research and development team and strengthen human resources to be adaptive to new and old competitors.